Smart City Readiness based on Smart City Council’s Readiness Framework - Kusuma Adi Achmad; Lukito Edi Nugroho; Achmad Djunaedi; Widyawan Widyawan (International Journal of Electrical and Computer Engineering (IJECE), 2018)
The level of urbanization which may impact on urban problems could be resolved through city development enabled and supported by the advanced ICT to build the city smart. To develop the city smart, the readiness of smart cities enablers should be assessed. The study was conducted based on pilot study through a survey on the smart city readiness. The analysis of smart city readiness in Yogyakarta showed that the evaluation of smart city projects implemented partially; only operational and asset optimization, and access to comprehensive device management implemented over 50%. Smart city readiness not only be measured by technological aspect but also need to be measured as non-technological aspects. Thus, measurement of readiness smart city can be more comprehensive.